The Effect Of Return On Asset, Debt To Equity Ratio, Current Ratio And Debt To Asset Ratio On Return On Equity: Case Study on S ector Companies Transportation and Logistics Listed on the IDX - Amelia, Rita (Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to determine and analyze the influence of Return On Assets (ROA), Debt To Equity Ratio (DER), Current Ratio (CR) and Debt to Asset Ratio (DAR) on Return on Equity (ROE) in sector transportation and logistics companies which is listed on the Indonesian Stock Exchange. This research uses quantitative methods with multiple regression models. The population used in this research is sector transportation and logistics companies listed on the IDX for the 2022-2023 period. The sample for this research was 16 Financial Reports of Logistics & Deliveries sub-industry companies (K211) for the period 2022 and 2023 so that a total of 32 data were studied in 2 years of observation. The data collection technique is documentation. The data analysis technique used in this research is the classic assumption test and multiple linear regression analysis using the SPSS V26 software tool. The hypothesis was tested partially using the t test. The partial research results show that ROA and DAR have a positive effect on ROE, DER has a negative effect on ROE while CR has no effect on ROE in logistics and delivery sub-industry companies listed on the IDX for the 2022-2023 period. Simultaneous hypothesis using the F test. Simultaneous research results show a significant influence between ROA, DER, CR, DAR on ROE in logistics and delivery sub-industry companies listed on the IDX for the 2022-2023 period.